An evidence-based review of enhanced recovery after surgery in total knee replacement surgery. Issue 9 (September 2019) - Ghosh, Arijit; Chatterji, Urjit
Rationale: Enhanced recovery after surgery is gaining popularity among orthopaedic surgeons across the globe and hence a strong evidence base had to be reviewed to make an evidence-based sustainable protocol. Methods: The following databases, PubMed, OVID, Cochrane database and EMBASE were searched. The search was limited to 15 components of enhanced recovery after surgery programme which is divided into preoperative, intraoperative and postoperative phases. Inclusion criteria were restricted to articles published in English within the last 15 years and articles comprising of unicompartmental arthroplasty, revision knee arthroplasty, bilateral simultaneous knee arthroplasty and only hip arthroplasty excluded. The full texts were analysed and controversies and limitations of various studies were summarised. Discussion: Each component of the programme was thoroughly reviewed and strength and weaknesses of the evidence base summarised. The strength of the evidence was assessed by critically appraising the study methodology and justifying the appropriateness of the inclusion in enhanced recovery after surgery protocol. Conclusion: Enhanced recovery after surgery has already been used successfully in various surgical specialities. Enhanced recovery after surgery programmes in knee arthroplasty are yet to be established as a universal practice to be adopted globally. This evidence-based review provides an insight into the best evidence linked to each component and their rationale for inclusion in the proposed enhanced recovery after surgery protocol.